The Study of Consumer Behavior on Online Food Ordering System in The Metropolitan City - Nur Ahmad Ruyani; Yana Sonjaya (Fakultas Ekonomi dan Bisnis, Universitas Papua., 2023)
The recent development of the Internet has boosted the extension of online food services by enabling people to search, compare prices and conveniently access these services. Because, only with an online system, small and medium-sized economic actors can compete with established food company such as McD and KFC. Therefore, it is important to know consumer behavior patterns from online food ordering systems for developing marketing strategies. Exploring online consumer behavior provides a better understanding of consumer segmentation in food demand and thus helps to lay the foundation for developing an online marketing strategy for competitive advantage. The purpose of this study is to finding factors affecting attitude towards online food retailing. This study uses a quantitative approach by involving respondents who often use online food ordering systems (Go-Food) applications in Bandung. The results showed that hedonic motivation and price saving orientation had no significant effect on behavior intention toward OFD services by Go-Food, while time saving orientation, prior online purchase experience and convenience motivation had a significant effect on behavior intention toward OFD services.